Glacial Ocean Map (GLOMAP) - André Paul; Stefan Mulitza; Ruediger Stein; Martin Werner (PANGAEA, 2020)
We present a climatology of the near-sea-surface temperature (NSST) anomaly and the sea-ice extent during the Last Glacial Maximum (LGM, 23,000-19,000 years before present) mapped on a global regular 1° exttimes1° grid. This is an extension of the Glacial Atlantic Ocean Mapping (GLAMAP) reconstruction of the Atlantic SST based on the results of the Multiproxy Approach for the Reconstruction of the Glacial Ocean Surface (MARGO) project and several recent estimates of the LGM sea-ice extent. The gridding of the sparse SST reconstruction was done in an optimal way using the Data-Interpolating Variational Analysis (DIVA) software, which takes into account the uncertainty on the reconstruction and includes the calculation of an error field. The climatology is provided as a Network Common Data Format (netCDF) file.